Fodder Potential of Multicut Pearlmillet Genotypes during Summer Season - Shashikala, T.; Rai, K. N.; Naik, R. Balaji; Shanti, M.; Chandrika, V.; Reddy, K. Loka (International Journal of Bio-resource and Stress Management, 2023)
Pearlmillet (Pennisetum americanum) is a quick growing, short duration food crop and an outstanding summer fodder crop of dry areas. Majority of recommended fodder pearlmillet varieties were evolved and released based on their single cut performance, but farmers are habituated to go for 2-3 cuts in. Therefore, an experimental study was taken up during summer 2008-09 at AICRP on Forage Crops, Hyderabad centre with nine pearl millet genotypes comprising of six varieties, two hybrids and one sorghum cultivar SSG (Jumbo) in a randomized block design with three replications to assess and identify the pearl millet genotypes having high fodder yield potential and also high nutritive value under multicut experimentation. The results revealed that among nine genotypes studied, the variety ICMV 08111 (811q ha-1) has recorded significantly high green fodder yield and it was on par with the genotypes ICMA 00999×ICMA 05444 (810 q ha-1) followed by Rijko Bajra (791 q ha-1), ICMV 05777 (784 q ha-1), ICMA 00999×IP 17315 (770 q ha-1), ICMV 05555 (720 q ha-1) than that of the check variety SSG (Jumbo 552 q ha-1). It is also observed that, there is no much significant difference in the green fodder yield potential between hybrids and varieties. On the other hand, the highest green fodder yields were recovered in second cut irrespective of the genotype.However, Rijko bajra (277 q ha-1) recorded highest dry fodder yield followed by ICMA 00999×ICMV 05444 (220 q ha-1). Rijko Bajra recorded high crude protein yield of 30.4 q ha-1.